Optimasi Biaya dan Waktu Dengan Metode TCTO pada Pembangunan Casting Mechanical & Civil Work For Oil Storage And Steady Room Workshop Gresik - Endriastuti, Alia Maharani; Triana, Masca Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
In planning a project in addition to time and resource variables, cost variables (costs) have a very important role. This research was conducted on the construction of Casting Mechanical &; Civil Work For Oil Storage And Steady Room Workshop Gresik. The purpose of this study is to obtain more efficient optimal cost and time using the Time Cost Trade Off (TCTO) method. This research is carried out by means of compression or emphasis on activities that are on a critical task. From the results of the analysis with the alternative of crashing the addition of working hours (overtime), it was found that the duration of the crashing results for 1 hour of overtime was 175 days, 2 hours of overtime 173 days, and 3 hours of overtime 172 days. As for the crash cost, 1 hour of overtime is Rp. 3,123,406,448 while 2 hours is Rp. 3,119,117,964 and 3 hours of overtime is Rp. 3,117,248,350. Of the three durations, it produces an optimal time of 172 working days with a time efficiency of 3.37% and an optimal cost of Rp. 3,117,248,350 with a cost efficiency of 0.42% with an overtime duration of 3 hours.